(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2013)
In and Against the State (1980), written by the London Edinburgh Weekend Return Group, is an exploration of the tensions experienced by the authors – all public sector workers – in their work. These tensions arose in particular from their commitment to promoting social justice and challenging capitalist systems and policies for the people that they worked with, whilst simultaneously being held accountable to state policy and processes. The term has since become representative of the often documented dichotomy in community development, whereby community workers are caught between the state and the community; between people and policies. In the current political climate, the popularity of community development in social policy and the use of community development values and language in the deployment of policy can be seen to cause a similar tension for community workers. This has seen the language of community development, such as ’community empowerment’, ’participation,’ and ’community’ itself, used across the political spectrum, often in ways which work against community development principles (Ledwith, 2011). This process has important consequences for community work and shows the on-going relevance of the ’in and against the state’ argument; that is, that the tensions experienced by community workers in mediating between the state and the community are still very much in evidence.